Gabriel García Márquez's «Eréndira» and the Brothers Grimm - Joel Hancock (Studies in 20th & 21st Century Literature, 1978)
García Márquez's long story «La increíble y triste historia de la Cándida Eréndira y de su abuela desalmada» is studied in the light of the structures and themes of the fairy tale, particularly of the type collected by the Grimm brothers. Dimensions of special interest are the organizational framework of the narrative, the portrayal of characters, and certain motifs, all of which are strongly reminiscent of Grimm's Fairy Tales. These elements are examined as representative of those morphologies which Vladimir Propp delineates for the genre of the fairy tale in his Morphology of the Folktale.
Keywords: Gabriel García Márquez; La increíble y triste historia de la Cándida Eréndira y de su abuela desalmada; Eréndia; fairy tales; Grimm brothers